Analisis Dampak Perubahan Tren Media Sosial terhadap Aktivitas Penjualan Online di Tiktok - Fita Aninda Sari; Darianto Darianto; Siti Musarofah; Mas’adah Mas’adah (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The rapid development of social media has significantly transformed digital marketing strategies, particularly for online businesses. TikTok has emerged as a powerful marketing platform due to its short-form video content and algorithm-driven system that promotes trending content through the For You Page (FYP). This study aims to analyze the impact of changes in TikTok social media trends on the sales activities of online businesses from the perspective of business actors. A qualitative descriptive approach was employed, with data collected through semi-structured in-depth interviews involving ten TikTok account owners who actively run online businesses or participate in the TikTok affiliate program. The findings indicate that the utilization of TikTok trends such as viral sounds, product reviews, tutorials, before–after content, and live streaming plays a crucial role in increasing product visibility, user engagement, purchase intention, and sales volume. Changes in trends encourage online business actors to continuously adapt their marketing strategies to remain relevant and competitive. In addition to positively influencing sales performance, TikTok trends also stimulate content creativity and help build consumer trust through high levels of interaction. However, business actors also face challenges, including rapidly changing trends, intense competition, and limitations in time and content consistency. Overall, this study concludes that changes in TikTok social media trends have a significant impact on online business sales activities and should be strategically and sustainably managed.